Efficient and Stable Carbon-coated Nickel Foam Cathodes for the Electro-Fenton Process. (10th September 2015) - Song, Shuqin; Wu, Mingmei; Liu, Yuhui; Zhu, Qiping; Tsiakaras, Panagiotis; Wang, Yi
Graphical Abstract: Highlights: Carbon-coated nickel foam (C@NF) was prepared by cycle coating carbon process. Ni leaching can be effectively controlled at C@NF4 (4 cycle coating times) cathode. C@NF4 exhibits excellent electro-Fenton performance with desirable stability. C@NF4 exhibits low energy consumption for DMP degradation. Abstract: Carbon-coated nickel foam (C@NF) electrodes are prepared via a simple and effective method, hydrothermal-carbonization cycle coating process, characterized by scanning electron microscopy (SEM) with energy dispersive spectrometer (EDS) and employed as the electro-Fenton (E-Fenton) cathode for degrading dimethyl phthalate (DMP) in aqueous solution. For the sake of comparison, nickel foam (NF) electrode and the conventional E-Fenton cathode (graphite gas diffusion electrode (GDE)) are also tested and compared. Experimental results indicate that nickel leaching can be effectively controlled at C@NF4 cathode (4 times cycle coating process), having great significance for promoting the application of NF in E-Fenton system. Moreover, C@NF4 cathode still presents excellent and effective performance on DMP degradation. DMP can be completely degraded within 2 h at −0.5 V and the total organic carbon (TOC) removal reaches as high as 82.1 %, which is almost 3 times as high as that at graphite GDE. Futhermore, the current efficiency for H2 O2 generation at C@NF4 is enhanced by 12 times compared to that at NF, and consequently the energy consumption during DMP degradation at C@NF4 is obvious lower than that at both NF cathode and graphite GDE. From the obtained results it can be deduced that C@NF4 is promising to be an attractive alternative E-Fenton cathode for removing organic pollutants in wastewater.